Dinamika dan Tantangan Demokrasi Pancasila dalam Konteks Sistem Ketatanegaraan Indonesia - Paramesti, Devita; Pratama, Sandro Gilang (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Pancasila democracy is a democratic system unique to Indonesia, rooted in the values of Pancasila, such as deliberation, social justice, and popular sovereignty. This research aims to examine the dynamics and challenges faced in the implementation of Pancasila democracy, especially related to the role of representative institutions, such as the MPR, DPR, and DPD. The method used is a literature study by reviewing various relevant journals and scientific articles published in the last five years to better understand the effectiveness of the functions of these representative institutions, the holding of simultaneous elections and the influence of the digital era on the quality of democracy are important focuses in this study. The results of this study show that although the principles of democracy have been affirmed in the 1945 Constitution, its implementation still faces serious challenges. Some of the problems that arise include money politics, polarization of opinions, low digital and political literacy, and the limited role of the Regional Representative Council (DPD). Therefore, it is necessary to improve regulation, public participation and education as an effort to strengthen the quality of democracy.